A new understanding of the microstructure of soot particles: The reduced graphene oxide-like skeleton and its visible-light driven formation of reactive oxygen species. (1st February 2021) - Zhu, Jiali; Shang, Jing; Zhu, Tong
Abstract: The mechanisms of soot's photochemistry are still unclear, especially, how the microstructure and composition of soot influence its photoactivity. In the current study, we started with the exploration of the microstructure of soot particles and gained new insights. The elemental-carbon fraction of soot (E-soot), considered the core component of soot and can reflect the intrinsic characteristics of soot, was extracted by organic solvents and characterized in terms of structure and chemical reactivity. The intrinsic structure of E-soot was found to be more analogous to reduced graphene oxide than to graphene, in terms of containing similar levels of defective sites such as oxygen-containing functional groups and environmentally persistent free radicals, as well as exhibiting similar optoelectronic performance. The generation of reactive oxygen species via an electron transfer pathway under visible light suggests that reduced graphene oxide-like E-soot can serve as a potential carbo-photocatalyst, which facilitates elucidating the mechanism of E-soot's role during soot's photochemical aging. Our study reveals the intrinsic structure of soot and its role in photo-triggered reactive oxygen species production, which is vital for atmospheric and health effects. Graphical abstract: Image 1 Highlights: The elementary unit of E-soot's microstructure is more like rGO than graphene. E-soot and rGO have similarities in the microstructure and optoelectronic properties. The intrinsic structure of E-soot contains defects including OFGs and EPFRs. Electron–hole pairs and ROS are formed in visible light-irradiated E-soot. Abstract : Soot containing reduced graphene oxide-like skeleton exhibits the ability of generating reactive oxygen species via an electron transfer pathway triggered by visible light.